1936
DOI: 10.1139/cjr36c-008
|View full text |Cite
|
Sign up to set email alerts
|

STRIPE RUST, PUCCINIA GLUMARUM, IN CANADA

Abstract: A study was made of the distribution of Puccinia glumarum (Schm.) Erikss. and Henn. in Canada, its specialization, host range, and reaction to environmental conditions. Unlike Puccinia graminis Pers., this rust has a limited distribution, being confined to British Columbia, Alberta, and the western half of Saskatchewan. The natural hosts include a number of native grasses, particularly Hordeum jubatum L. and certain species of Agropyron, Elymus, and Bromus. Wheat and barley also become infected although to a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The presented results were also consistent with previous studies performed on other plant diseases. Such as, it was reported that pre-inoculation temperature at 12.9°C often increased susceptibility in wheat to stripe rust [41]. It was also reported that tobacco callus cultures inoculated with tobacco mosaic virus (TMV) and soybean callus cultures inoculated with southern bean mosaic virus (SBMV) revealed a higher rate of virus synthesis held for 4 days at 10°C than those continuously maintained at 24°C [42].…”
Section: Discussionmentioning
confidence: 95%
“…The presented results were also consistent with previous studies performed on other plant diseases. Such as, it was reported that pre-inoculation temperature at 12.9°C often increased susceptibility in wheat to stripe rust [41]. It was also reported that tobacco callus cultures inoculated with tobacco mosaic virus (TMV) and soybean callus cultures inoculated with southern bean mosaic virus (SBMV) revealed a higher rate of virus synthesis held for 4 days at 10°C than those continuously maintained at 24°C [42].…”
Section: Discussionmentioning
confidence: 95%
“…. Similarly wheat plants susceptible to stripe rust at 12 .9°C became resistant when exposed to a temperature of 25 .3°C (NEWTON & JOHNSON, 1936) . SHARP (1962) demonstrated that, depending on the cultivar, wheat plants grown at 24°C before inoculation with Puccinia striiformis (syn .…”
Section: Resultsmentioning
confidence: 99%
“…In subsequent years, it was found in British Columbia, southern Alberta, and western Saskatchewan but was not found during that time in Manitoba or eastern Saskatchewan (Newton and Johnson 1936). The main area of concern for stripe rust in Canada has been southern Alberta, where it is an annual production problem.…”
Section: Introductionmentioning
confidence: 99%
“…The disease was particularly devastating in Alberta in 2005, when severities of up to 100%, based on a modified Cobb's scale (Peterson et al 1948), were observed in some wheat nurseries, resulting in premature ripening of portions of the heads and prolific production of urediniospores between kernels and glumes (McCallum et al 2006). Although it was demonstrated that the rust can overwinter in Alberta (Conner et al 1988), the primary source of inoculum was thought to be windborne urediniospores from the adjoining states of Montana, Idaho, and Washington (Newton and Johnson 1936). Stripe rust was not reported in the eastern Prairie regions of Manitoba or Saskatchewan in Canada until 2000 (Fetch and McCallum 2001).…”
Section: Introductionmentioning
confidence: 99%